Degeneracy in epilepsy: multiple routes to hyperexcitable brain circuits and their repair - Stöber, Tristan Manfred; Batulin, Danylo; Triesch, Jochen; Narayanan, Rishikesh; Jedlicka, Peter; Justus Liebig University Giessen (My University, 2023)
Due to its complex and multifaceted nature, developing effective treatments for epilepsy is still a major challenge. To deal with this complexity we introduce the concept of degeneracy to the field of epilepsy research: the ability of disparate elements to cause an analogous function or malfunction. Here, we review examples of epilepsy-related degeneracy at multiple levels of brain organisation, ranging from the cellular to the network and systems level. Based on these insights, we outline new multiscale and population modelling approaches to disentangle the complex web of interactions underlying epilepsy and to design personalised multitarget therapies.
Keywords: ddc:610